2015
DOI: 10.1093/ndt/gfu400
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic nephrocalcinosis in chronic kidney disease patients

Abstract: Our data demonstrate that prevalence rates of nephrocalcinosis increase with increasing CKD stage to reach more than 50% in end-stage renal disease patients and suggest that acid-base and mineral metabolism disturbances are implicated in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
8
17
1
Order By: Relevance
“…Renal mineralization is a complicated and multifaceted process and its pathogenesis in association with CKD remains unclear. However, increasing evidence suggests that mineral metabolism disturbances, particularly calcium and phosphate, are likely to contribute to nephrocalcinosis 11,12 . In our study, higher plasma tCa at CKD diagnosis, even with tCa within the reference interval, was an independent nephrocalcinosis risk factor; only 1 (2%) cat had total hypercalcemia at baseline.…”
Section: Discussionmentioning
confidence: 41%
“…Renal mineralization is a complicated and multifaceted process and its pathogenesis in association with CKD remains unclear. However, increasing evidence suggests that mineral metabolism disturbances, particularly calcium and phosphate, are likely to contribute to nephrocalcinosis 11,12 . In our study, higher plasma tCa at CKD diagnosis, even with tCa within the reference interval, was an independent nephrocalcinosis risk factor; only 1 (2%) cat had total hypercalcemia at baseline.…”
Section: Discussionmentioning
confidence: 41%
“…Phosphate nephropathy and nephrocalcinosis are also likely under-recognized causes of ongoing loss of GFR 50, 51 . A recent study by Evenepoel et al demonstrated that microscopic nephrocalcinosis was quite common in patients with CKD and prevalence increased with worsening glomerular filtration rate and correlated with elevated serum phosphate and parathyroid hormone levels 52 . It is likely that OPN is involved in this process as Lorenzen et al discovered that OPN levels increased with worsening GFR 53 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar association between kidney function and prevalence of microscopic nephrocalcinosis was observed in a more recent renal biopsy study. Nephrocalcinosis (almost exclusively calcium phosphate crystals) was found in 4.6% of deceased kidney donors, compared with 14.3%, 20.2%, and 54% for stages 1–2 CKD, stages 3–4 CKD, and stage 5 CKD or ESRD, respectively (44). According to the precipitation-calcification hypothesis, calcium phosphate crystal deposition in the renal parenchyma may lead to further inflammation and kidney injury (99).…”
Section: Calcium Phosphate Deposition In Human Renal Biopsy Tissuementioning
confidence: 99%
“…Elevations in PTH may increase cytosolic calcium in the tubules and contribute to the pathogenesis of nephrocalcinosis (44, 73, 99). Observational studies have shown associations between elevated FGF23 levels and an increased risk of CKD progression (51, 106, 128, 141).…”
Section: Fgf23 and Pth: Potential Mediators Of Adverse Effects Of Higmentioning
confidence: 99%